Shape memory micro-anchors with magnetic guidance for precision micro-vascular deployment. (April 2022) - Li, Zhihua; Chen, Zijian; Gao, Yanan; Xing, Yi; Zhou, Yuping; Luo, Yucheng; Xu, Weihong; Chen, Zhengchang; Gao, Xu; Gupta, Kapish; Anbalakan, Karthic; Chen, Lei; et al.
Abstract: Transcatheter medical micro-devices through circulatory system show great potential for therapy but lack strategies to stably anchor them at the desired site in vascularized tissues to take actions. Here a shape memory functionalized biodegradable magnetic micro-anchor (SM 2 A) is developed to achieve magnetic guided endovascular localization through precisely controlled shape transformation. The SM 2 A comprises anisotropic polylactide-based microparticle embedded with superparamagnetic Fe3 O4 nanoparticles, exhibiting thermally activated tunable shape recovery modes at a body-friendly temperature range to accomplished an efficient endovascular anchoring effect in both decellularized liver organ and rabbit ear embolization models. The SM 2 A can be anchored at the target micro-vessel, exhibiting a controlled radial expansion of the vessel wall yielding with estimated stresses of 7–26 kPa in contact stress and 38–218 kPa in von Mises stress. The SM 2 A is a promising platform to incorporate diagnostic or therapeutic agents for precision deployment and in-situ action.